Modelos de riesgo de crédito: Aplicación práctica a un modelo de refinanciación de hipotecas; Credit risk models: Practical application to a mortgage refinancing model - Caro Barrera; José Rafael (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2019)
– Facing an hypothetical, but increasingly, case of default risk on a mortgage or a fall in interest rates, an important issue raised by the borrower is the possibility of minimizing that risk by selecting the best refinancing option. In this paper, a mortgage refinancing model is presented, developing a purely quantitative programming method with a simulation based on an algorithm created especially for this case and that can be useful for mortgage debtors. Thus, we begin by explaining the theoretical basis on which the research is based, to proceed to develop the problem, continuing with its implementation. Finally, the results are analyzed and the most relevant conclusions are commented.
Keywords: C02; C61; C63; 330; credit risk; dynamic optimization; dynamic programming; interest rate; mortgage refinancing; mortgaged backed securities; Basel III